Market Equilibrium and the Environmental Effects of Tax Adjustments in China's Automobile Industry - Xiao, Junji; Ju, Heng (The Review of Economics and Statistics, 2014)
This paper explores the effects of consumption-tax and fuel-tax adjustments in the Chinese automobile industry. Applying the model and simulation method of Berry, Levinson, and Pakes (1995), we conduct a comparative static analysis of equilibrium prices and sales, fuel consumption, and social welfare before and after tax adjustments. For the first time, we compare the progressivity of both taxes. Our empirical findings suggest that the fuel tax is effective in decreasing fuel consumption at the expense of social welfare, while the consumption tax does not significantly affect either fuel consumption or social welfare.